2019
DOI: 10.1055/s-0037-1611460
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Phosphonic Acids as Potent Tools to Study Phosphonate Enzymology

Abstract: Phosphonic acids are highly stable phosphorus-containing compounds, which have been proposed as important intermediates in the global phosphorus cycle. Biogenic phosphonates as well as their synthetic analogues play an important role as potential enzyme inhibitor drugs and as alternative phosphorus source for microbes. Despite these properties, their metabolism is still poorly understood. New degradative pathways and unknown compounds are identified at fast pace. However, most of these pathways include a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Indeed, the search for such new pathways is actively pursued in the field, one of the major hurdles being the accessibility of biogenic phosphonates, which are often commercially unavailable or (when available) very expensive and not enantiomerically pure. 53 While the work presented here does not describe a completely new route for phosphonate breakdown, it does describe a novel enzyme, apparently “invented” by evolution to increase the utility of the common (but otherwise very specialized) hydrolytic pathway for AEP degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the search for such new pathways is actively pursued in the field, one of the major hurdles being the accessibility of biogenic phosphonates, which are often commercially unavailable or (when available) very expensive and not enantiomerically pure. 53 While the work presented here does not describe a completely new route for phosphonate breakdown, it does describe a novel enzyme, apparently “invented” by evolution to increase the utility of the common (but otherwise very specialized) hydrolytic pathway for AEP degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that even some human-made phosphonates, which have been introduced recently and often cause environmental pollution, can be exploited as phosphorus sources by some bacteria. , These studies have characterized several pathways for phosphonate breakdown and implied that additional ones must exist. Indeed, the search for such new pathways is actively pursued in the field, one of the major hurdles being the accessibility of biogenic phosphonates, which are often commercially unavailable or (when available) very expensive and not enantiomerically pure . While the work presented here does not describe a completely new route for phosphonate breakdown, it does describe a novel enzyme, apparently “invented” by evolution to increase the utility of the common (but otherwise very specialized) hydrolytic pathway for AEP degradation.…”
Section: Discussionmentioning
confidence: 99%
“…They are formed by the action of specific flavin-dependent, oxime-forming N-oxidases. These oxidases are also able to convert the oximes 50 and 51 into corresponding nitroethylphosphonates (compounds 52 and 53) [96]. Structures of these intermediates and side products are depicted in Figure 7.…”
Section: Phosphonopeptide Antibioticsmentioning
confidence: 99%
“…Through a combination of bioinformatics, enzymology and organic chemistry 28 , we have identified and functionally characterized a PLP-dependent enzyme, termed PbfA, which is generally annotated in public databases as GABA-T. Recurrence of pbfA in gene clusters dedicated to AEP degradation had been incidentally noted before 4,6 , but without any experimental follow-up.…”
Section: Discussionmentioning
confidence: 99%